FULLY SUBSTITUTED CARBON CENTERS BY DIASTEREOSELECTIVE SPIROCYCLIZATION: STEREOSELECTIVE SYNTHESIS OF (+)-LEPADIFORMINE C - Perry, Matthew A. (2010)
Reductive lithiation of N-Boc α-amino nitriles generated α-amino alkyllithium reagents with unexpected selectivity. The intermediate radical prefers to align with the nitrogen lone pair, and this interaction leads to an A(1,3)-strain effect that biases the conformation of the radical. In cyclohexane rings with α-substituents the net effect is an inversion of configuration on reductive lithiation. In the presence of a tethered electrophile the alkyllithium cyclizes to produce a spiro compound, again with inversion of configuration. The overall result is retention of configuration in the cyclization reaction. The same overall selectivity is found with α-oxygen alkyllithium cyclizations, but in this case both steps proceed with retention. The difference can be explained by careful consideration of the intermediate geometries. The α-amino spirocyclization was utilized in a concise and stereoselective synthesis of lepadiformine C.